THE ANALYSIS OF THE COMPETITIVENESS OF RUSSIAN UNIVERSITIES IN WORLD RANKINGS - Svetlana S. Donetskaya (Высшее образование в России)
In July 2013, fifteen Russian universities had won the competition for public support for entry into the world rankings. Every university in this group is well known in Russia and has a high reputation among Russian academic and business community. At the same time, these universities have different starting positions and unequal possibilities for successful competition in the global educational space. The paper examines the current state of Russian universities and identifies ways to improve thecompetitiveness of Russian universities in international rankings.